(untitled) (International Seven Journal of Multidisciplinary, 2024)
The purpose of this article is to present the main aspects highlighted in the work Educational Neuroscience: Initiatives and Emerging Issues organized by Katheryn E. Patten and Stephen R. Campbell, director of the Engrammetron laboratory (Educational Neuroscience and Mixed Research Laboratory). The choice of this theme is justified by the need to deepen the research, carried out by me, on mathematical concepts inherent to the constitution of the mathematical mind of individuals. In this study, carried out in 2017, I was able to show that this term is associated not only with the mathematical structure conceived by the community, but also with the mental biological structure (TALL, 2000). Therefore, it is possible to say that we are entering the multiprocessable, active and participatory system that corresponds to the human brain.